2015
DOI: 10.1038/nplants.2015.138
|View full text |Cite
|
Sign up to set email alerts
|

Intensity of a pulse of RSL4 transcription factor synthesis determines Arabidopsis root hair cell size

Abstract: Cell size is determined by the duration and rate of growth and plays a central role in cell function. Root hairs are tip-growing cellular projections that emerge from the root epidermis and explore the soil to acquire nutrients and water(1). Previously we demonstrated that the basic helix-loop-helix transcription factor root hair defective 6-like 4 (RSL4) is necessary and sufficient for root hair growth(2). Here we show that RSL4 is synthesized in a 4-h pulse at the initiation of hair elongation and is gradual… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
116
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 103 publications
(119 citation statements)
references
References 17 publications
3
116
0
Order By: Relevance
“…RH determination and elongation in Arabidopsis is controlled (in part) by a small family of basic HelixLoop-Helix transcription factors that includes the auxin-inducible gene member RSL4 (14-16). Datta et al (17) have recently shown that RH length is proportional to RSL4 mRNA abundance. Significantly, qRT-PCR analysis revealed that dao1-1 and dao1-3 seedlings contained an ∼80% increase in RSL4 transcript levels (Fig.…”
Section: Iaa Oxidation In Arabidopsis Is Controlled By the Dioxygenasmentioning
confidence: 99%
“…RH determination and elongation in Arabidopsis is controlled (in part) by a small family of basic HelixLoop-Helix transcription factors that includes the auxin-inducible gene member RSL4 (14-16). Datta et al (17) have recently shown that RH length is proportional to RSL4 mRNA abundance. Significantly, qRT-PCR analysis revealed that dao1-1 and dao1-3 seedlings contained an ∼80% increase in RSL4 transcript levels (Fig.…”
Section: Iaa Oxidation In Arabidopsis Is Controlled By the Dioxygenasmentioning
confidence: 99%
“…RSL4 is a direct target of ROOT HAIR DEFECTIVE 6 (RHD6), a VIIIc subfamily bHLH transcription factor that promotes the early stages of root hair development, and is suggested to represent the conversion point of internal and environmental cues (Masucci and Schiefelbein, 1996). RSL4 is expressed in Arabidopsis trichoblasts in the elongation zone immediately prior to initiation of root-hair outgrowth, and it controls a suite of genes encoding proteins that are required for root hair morphogenesis (Yi et al, 2010;Datta et al, 2015). Of note, RSL4 is rapidly degraded after root hair elongation is initiated; Pi deficiency significantly increases the synthesis and half-life of RSL4 (Datta et al, 2015).…”
Section: The Control Of Root Hair Elongation and Lengthmentioning
confidence: 99%
“…Pi deficiency-induced prolonged growth of root hairs is directly correlated with the intensity of a translational pulse of the bHLH transcription factor ROOT HAIR DEFECTIVE 6-LIKE 4 (RSL4) (Yi et al, 2010;Datta et al, 2015). RSL4 is a direct target of ROOT HAIR DEFECTIVE 6 (RHD6), a VIIIc subfamily bHLH transcription factor that promotes the early stages of root hair development, and is suggested to represent the conversion point of internal and environmental cues (Masucci and Schiefelbein, 1996).…”
Section: The Control Of Root Hair Elongation and Lengthmentioning
confidence: 99%
See 1 more Smart Citation
“…The length is critically dependent on the activity of the transcription factor ROOT HAIR DEFECTIVE 6-LIKE 4 (RSL4), which is necessary and sufficient for root hair growth (Datta et al, 2015). The elongation time and the growth rates are promoted under Pi deficiency, leading to longer root hairs in the Arabidopsis accession Col-0 (Bates and Lynch, 1996).…”
Section: Introductionmentioning
confidence: 99%